Outcome of Infected Cardiac Device Re-implantation in Erbil Cardiac Center-Iraq - Mohammed Hasan Alwan (Advanced Medical Journal)
Background & Objectives: Cardiac electronic devices have been   in clinical practice for more than 6 decades. Infection is not uncommon with these devices due to their scarcity and exorbitant cost which makes them inaccessible to a significant number of patients. Therefore, the only method to source them is to reimplant used devices. The problem of possible infection as result of reusing these devices has not been previously investigated in Iraq. The objective of the current study was to find the outcomes of the re-implanted infected device.